TALKING KRISHNA – DEVELOPING 3D CHARACTER OF KRISHNA - Brigitta Violena Mahardika; Artiarini Kusuma Nurindiyani; Hestiasari Rante; Fardani Annisa Damastuti; Budi Berlinton Sitorus (Institut Bisnis dan Informatika Kwik Kian Gie, 2021)
The Children who are born in the latest generation are called the Z and Alpha generations. These generations are the ones closest to the Internet and technology. The current advance of technology makes global connections even more widespread so that the need for an international language to communicate is also urgently needed. Therefore, an interactive educational application that uses English as the international language was created using Krishna's character as the main character. This interactive application is named Talking Krishna. This character of Krishna was designed as attractive as possible so that children can easily grasp the knowledge offered by Talking Krishna. Besides, Krishna's character will deliver some of the moral values that are believed can improve the children’s character building. Krishna's character is made by utilising 3D animation with Cinema 4D. Keywords— 3D animation, 3D modelling, Krishna